2018
DOI: 10.1038/s41598-018-36099-4
|View full text |Cite
|
Sign up to set email alerts
|

Connectivity of the Superficial Muscles of the Human Perineum: A Diffusion Tensor Imaging-Based Global Tractography Study

Abstract: Despite the importance of pelvic floor muscles, significant controversy still exists about the true structural details of these muscles. We provide an objective analysis of the architecture and orientation of the superficial muscles of the perineum using a novel approach. Magnetic Resonance Diffusion Tensor Images (MR-DTI) were acquired in 10 healthy asymptomatic nulliparous women, and 4 healthy males. Global tractography was then used to generate the architecture of the muscles. Micro-CT imaging of a male cad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…On its anterior side, the EAS passed the superficial transverse perineal and bulbospongious muscles superficially in the female (Wu et al, ), while a midline spur extended even further anteriorly in the male (Arakawa et al, ; Wu et al, ). We cannot exclude that some muscle fibers connect EAS and bulbospongious muscle, as reported recently in a diffusion tensor‐imaging study of perineal muscles (Zifan et al, ). However, the putative exchange area only accounted for <25% of the height of the EAS.…”
Section: New Findingsmentioning
confidence: 74%
“…On its anterior side, the EAS passed the superficial transverse perineal and bulbospongious muscles superficially in the female (Wu et al, ), while a midline spur extended even further anteriorly in the male (Arakawa et al, ; Wu et al, ). We cannot exclude that some muscle fibers connect EAS and bulbospongious muscle, as reported recently in a diffusion tensor‐imaging study of perineal muscles (Zifan et al, ). However, the putative exchange area only accounted for <25% of the height of the EAS.…”
Section: New Findingsmentioning
confidence: 74%
“…In the current study, we confirmed the feasibility of DTI in the evaluation of pelvic floor muscles. To date, previous reports described application of DTI for evaluation of female pelvic floor muscles [ 18 - 20 , 22 ] as well as in the internal and external urinary sphincter muscles in healthy males [ 23 ]. However, to our knowledge, we are the first to investigate application of DTI acquired in 30-second frames for isometric resolution of 3×3×3 mm3.…”
Section: Discussionmentioning
confidence: 99%
“…In the muscle fibers, the diffusivity of water is larger in the direction parallel to dominant muscle fibers. Since MD expresses the average and FA the largest directionality of water molecules in random motion, the muscle architecture and function can be assessed indirectly [ 20 , 24 , 25 ]. As we observed an increase in MD during contraction of pelvic muscles, the effect might have been caused by higher uniformity of the muscle orientation compared to that during rest.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations